Toward a Cytological Characterization of the Rice Genome - Cheng, Zhukuan; Buell, C. Robin; Wing, Rod A.; Gu, Minghong; Jiang, Jiming (Genome Research, 2001)
Rice (Oryza sativa L.) will be the first major crop, as well as the first monocot plant species, to be completely sequenced. Integration of DNA sequence-based maps with cytological maps will be essential to fully characterize the rice genome. We have isolated a set of 24 chromosomal arm-specific bacterial artificial chromosomes to facilitate rice chromosome identification. A standardized rice karyotype was constructed using meiotic pachytene chromosomes ofO. sativa spp. japonica rice var. Nipponbare. This karyotype is anchored by centromere-specific and chromosomal arm-specific cytological landmarks and is fully integrated with the most saturated rice genetic linkage maps in which Nipponbare was used as one of the mapping parents. An ideogram depicting the distribution of heterochromatin in the rice genome was developed based on the patterns of 4',6-diamidino-2-phenylindole staining of the Nipponbare pachytene chromosomes. The majority of the heterochromatin is distributed in the pericentric regions with some rice chromosomes containing a significantly higher proportion of heterochromatin than other chromosomes. We showed that pachytene chromosome-based fluorescence in situ hybridization analysis is the most effective approach to integrate DNA sequences with euchromatic and heterochromatic features.
10.1101/gr.194601